1999
DOI: 10.1046/j.1365-3040.1999.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive nature of the transition phases in development: the case of Sorghum bicolor

Abstract: An increase in tolerance to salinity is induced in Sorghum bicolor by exposure to a sublethal concentration of NaCl during early vegetative development. The phase of competence for induction of this response, termed salt adaptation, is well defined in time and it coincides with the emergence of the first adventitious roots. The link between these events was investigated. Competence for salt adaptation varies among genotypes. It is shown that competence is especially high for genotypes in which the link between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…This process was clearly observed during normal development (Amzallag 1999d(Amzallag , 2001b. As shown in S. bicolor, physiological adaptation to salinity (expressed exclusively during a developmental window, see Amzallag, Seligmann & Lerner 1993) is also clearly related to the decrease in organ connectance during the early vegetative critical period (Amzallag 1999d). It is likely that the adaptive properties inherent to developmental plasticity (Sultan 1995) are an expression of this phenomenon.…”
Section: Network Regulations and Adaptive Plasticitymentioning
confidence: 76%
See 2 more Smart Citations
“…This process was clearly observed during normal development (Amzallag 1999d(Amzallag , 2001b. As shown in S. bicolor, physiological adaptation to salinity (expressed exclusively during a developmental window, see Amzallag, Seligmann & Lerner 1993) is also clearly related to the decrease in organ connectance during the early vegetative critical period (Amzallag 1999d). It is likely that the adaptive properties inherent to developmental plasticity (Sultan 1995) are an expression of this phenomenon.…”
Section: Network Regulations and Adaptive Plasticitymentioning
confidence: 76%
“…Although resulting from mathematical transformations, connectance reflects biological phenomena. Changes in connectance were observed during specific phases of development in Sorghum, and they were related to the adaptive phenotypic plasticity of the plant (Amzallag & Seligmann 1998;Amzallag 1999d). Connectance is also affected by hormonal treatments (CK and GA) even before any significant effect on growth (Amzallag 1999c(Amzallag , 2001a).…”
Section: Two-dimension Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The number of these discrete stages itself depends on the interaction between developmental and environmental constraints. In Sorghum bicolor, a linkage was previously observed between salt-adaptation and events occurring during specific transition phases in normal development (Amzallag 1999). I concluded that normal development includes adaptive events, so environment cannot be restricted to a trigger for the expression of a pre-existing genetic programme.…”
Section: Adaptation and Individuationmentioning
confidence: 89%
“…Grain yield also depends on developmental processes such as meristem differentiation, meiosis or pollination, which are not directly related to the plant leaf area. In sorghum, Amzallag (1999) showed that the plant sensitivity to environmental stresses depends on the hormonal metabolism integrating the different meristems within the whole organism. This functional integration of the various meristems depends on the timing of morphogenesis, which could explain the irreparable damage on final grain production caused by environmental stress during earlier phases of development.…”
Section: Discussionmentioning
confidence: 99%